Adverse Perinatal Outcomes Associated with True Knot of the Umbilical Cord: A Multicenter Retrospective Study - Bas Lando, Maayan; Sela, Hen Y.; Helman, Sarit; Shapira, Eliel; Grisaru-Granovsky, Sorina; Rottenstreich, Misgav (American Journal of Perinatology, 2025)
This study aimed to estimate the prevalence of true knot of the umbilical cord (TKUC) and identify associated adverse maternal and neonatal outcomes.A multicenter retrospective cohort study was conducted, including all women with singleton pregnancies who delivered between 24 and 42 weeks of gestation from 2005 to 2021 at two large obstetrical centers. Gross pathological examinations of the placenta and umbilical cord were routinely performed immediately after delivery. Women with TKUC detected postpartum were compared with those without TKUC. Maternal and neonatal characteristics, along with adverse outcomes, were compared between the two groups.During the study period, 283,055 deliveries met inclusion and exclusion criteria. The incidence of TKUC was 1.3%, intrauterine fetal death (IUFD) rate was significantly higher in the TKUC group (1.8% vs. 0.3%), with 91% of these deaths occurring after 34 weeks of gestation, and 72% occurring after 37 weeks. Women with TKUC experienced higher rates of preterm premature rupture of membranes, premature rupture of membranes, induction of labor, meconium-stained amniotic fluid, vacuum-assisted vaginal delivery, and postpartum hemorrhage. The rate of intrapartum cesarean deliveries was similar between the groups. Neonatal outcomes revealed similar birth weights, but higher rates of small-for-gestational-age neonates, low Apgar scores, jaundice, hypoglycemia, and intracranial hemorrhage in the TKUC group. Multivariate analysis demonstrated that TKUC was independently associated with IUFD (adjusted odds ratios [aOR]: 6.07; 95% confidence intervals [CI]: 4.68–7.86, p < 0.01).TKUC is not uncommon and is associated with an increased risk of IUFD, particularly in the late third trimester, as well as adverse neonatal outcomes. Early diagnosis in the third trimester followed by delivery in the late preterm or early term period may reduce IUFD rates.
Keywords: true knot of the umbilical cord; intrauterine fetal death; adverse neonatal outcomes; prevalence; multicenter retrospective cohort; pathological examination